Impact of spatial variation of a crucial prey, the molecricket, on hoopoe territory occupancy and reproduction. (12th May 2016) - Guillod, Nicolas; Arlettaz, Raphaël; Jacot, Alain
Abstract : Direct benefits accrued from securing a territory of sufficient quality are important determinants of individual fitness and population persistence. Food supply is one of the main factors of animal territory quality, with spatial and temporal variation in prey availability largely dictating reproductive output and thus population dynamics. In a Swiss hoopoe population, molecrickets Gryllotalpa gryllotalpa, the most profitable prey locally, can constitute most of the food biomass delivered to chicks by parents. We first investigated the impact of molecricket prey on hoopoes' fitness‐related traits by quantifying the spatial variation in the food allocation pattern of both male and female parents to chicks across the whole population range; and second, analysed the impact of this prey on current reproduction and, using a 11 yr dataset, on the temporal occupancy rate of each territory. We found considerable but spatially repeatable variation, over the years, of molecricket biomass in the diet provisioned to chicks. This spatial heterogeneity in chicks' diet composition was mirrored both in the history of territory occupancy (2002–2012) and in current reproductive success (2012). Territories with a greater biomass of molecrickets in chicks' diet produced more fledglings in better body condition. Yet, these effects on current reproduction were exclusively demonstrated for male parents, corroborating that paternal provisioning patterns play a predominant role in hoopoe reproductive success. This study demonstrates how a single, very profitable prey species might affect spatial variation in territory settlement and individual reproductive success in a regionally endangered bird species, with potential consequences for its population dynamics and persistence.